Biochemical Profiling for Antioxidant and Therapeutic Potential of Pakistani Chickpea (Cicer arietinum L.) Genetic Resource - Jameel, Saima; Hameed, Amjad; Shah, Tariq Mahmud (Frontiers in Plant Science, 2021)
In Pakistan, chickpea (Cicer arietinumL.) is the largest grown legume crop, especially in desert areas. Along with an excellent source of nutrition, chickpea seeds have discernible medicinal and antioxidant characteristics. The diverse set of 90 chickpea genotypes (66 desi and 24 kabuli) were collected from different research zones of Pakistan, and seed flour was used for biochemical profiling. Genotypes were significantly different (Tukey HSD test, P < 0:05) for the traits under investigation. In non–enzymatic antioxidants, highest seed total phenolic contents (TPC) (34725± 275 µM/g s. wt.) was found in CM-98 (desi), ascorbic acid (AsA) (69.23±2.25 µg/g s. wt.) in WH-3 (desi) , and total flavonoids contents (TFC) (394.98± 13.06 µg/mL sample) was detected in WH-11 (desi). In the class of enzymatic antioxidants, the highest seed ascorbate peroxidase (APX) (1680±40 Units/g s. wt.) was detected in Tamman-2013 (kabuli), peroxidases (POD) (2564.10±233.10 Units/g s. wt.) activity in CM1235/08 (desi), and superoxide dismutase (SOD) (279.76±50 Units/g s. wt.) was detected in CH24/11 (desi). Highest seed catalase activity (CAT) (893±50 Units/g s. wt.) and proline content (272.50±20.82 µg/g s. wt.) was detected in a ICC-4951 (desi). In hydrolytic enzymes, the highest activity of esterase (37.05µM/min/g s. wt) was found in, CH56/09(Kabuli), protease (11080±10 Units/g s. wt.) in Karak-2 (desi), and α-amylase (213.02±3.20 mg/g s. wt.) was observed in CH74/08 (kabuli). In other biochemical parameters, the highest seed total oxidant status (TOS) (356±17.50 µM/g s. wt.) was detected in CM3457/91 (desi), malondialdehyde (MDA) content (295.74±3.097 uM/g s. wt.) was observed in CM-2008(kabuli), and total antioxidant capacity (TAC) (8.36± 0.082 µM/g s. wt.) was found in CM-72 (desi). In case of pigment analysis, Sheenghar-2000 (desi) depicted highest lycopene (12.579± 0.313 µg/g s. wt.) and total carotenoids (58.430.23±0.569 µg/g s. wt.) contents. For seed therapeutic potential, the highest seed α-amylase inhibition (82.33±8.06 %) was observed in CM-88 (desi), while WH-1, WH-6, and ICCV-96030 (desi) depicted the highest value for seed anti-inflammatory potential (78.88±0.55%). Genotypes with highest antioxidant and therapeutic potential can be utilized as natural antioxidant source and in breeding programs aimed to improve these traits in new breeding lines.